Anti-diabetic effect of amorphastilbol through PPAR alpha/gamma dual activation in db/db mice - Lee, Woojung; Ham, Jungyeob; Kwon, Hak Cheol; Kim, Yong Kee; Kim, Su-Nam (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2013)
Peroxisome proliferator-activated receptors (PPARs) have been considered as desirable targets for metabolic syndrome treatments, even though their specific agonists have several side effects, including body weight gain, edema, and tissue failure. The effects of amorphastilbol (APH) on glucose- and lipid metabolism were investigated with in vitro 3T3-L1 adipocyte systems and in vivo db/db mice model. APH selectively stimulates the transcriptional activities of both PPAR alpha and PPAR gamma, which are able to enhance fatty acid oxidation and glucose utilization. Furthermore, APH improves glucose and lipid impairment in db/db mice. More importantly, there are no significant side effects, such as weight gain or hepatomegaly, in APH-treated animals, implying that APH do not adversely affect liver or lipid metabolism. All our data suggest that APH can be used as potential therapeutic agents against type 2 diabetes and related metabolic disorders, including obesity, by enhancing glucose and lipid metabolism. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: FREE FATTY-ACIDS; TYPE-2 DIABETES-MELLITUS; LIPID-METABOLISM; EXPRESSION; INSULIN; GLUCOSE; AGONIST; OBESITY; WEIGHT; RISK